Compacted Dry Biocellulose Formulated from Xanthosoma Undipes K. Koch (Taro): Characterization of Physical and Chemical Properties - Septia Ardiani; Handika Dany Rahmayanti; Nurul Akmalia; Annisa Jasmine (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the physical properties of compacted dry biocellulose derived from Xanthosoma undipes K. Koch (taro). Three types of substrates were fermented using Acetobacter xylinum: nata de taro (NDT), nata de coco-taro (NDC-T), and nata de coco-taro-pineapple-tomato (NDC-TPT). The resulting biocellulose products were compacted using a hot press (5000 kgf/cm² for approximately 15 minutes at 120°C) and then dried at 30°C to produce solid biopolymer sheets. Characterization included thickness measurement, FTIR spectroscopy, UV-Vis spectroscopy, and SEM-EDX microscopy. Results showed that the cellulose chemical structure remained intact after compaction. The NDC-TPT sample exhibited the highest porosity and water absorption capacity, along with significant UV light transmittance, making it a promising candidate for biodegradable film applications and active moisture-absorbing materials. Microscopic analysis revealed that substrate composition strongly influenced fiber density and pore size, with NDT showing the densest structure and NDC-TPT the most porous.